In vivo toxicity and antioxidant of pressurize hot water Phyllanthus tenellus Roxb. extracts - Yeap, Swee Keong (BMC Complement Med Ther, 2021)
BACKGROUND: Phyllanthus tenellus Roxb. has been traditionally used to treat inflammation and liver diseases and its medicinal property may be due to the presence of relatively high levels of hydrosable tannins. Recent report revealed that pressurized hot water extraction of P. tenellus significantly increased the concentration of hydrolysable tannins and its catabolites. Thus, this study was aimed to evaluate the in vivo toxicity and antioxidant capacity of pressurized hot water extraction of P. tenellus on healthy mice. METHODS: Pressurized hot water extraction P. tenellus was carried out and standardized to 7.9% hydrosable tannins. In vitro toxicity of the extract was tested on NIH 3 T3 cell by MTT assay. The cellular antioxidant level was quantified by measuring cellular level of glutathione. Oral sub-chronic toxicity (200, 1000 and 3000 mg/kg body weight) of P. tenellus extract were evaluated on healthy mice. Liver and kidney antioxidant level was quantified by measuring levels of Ferric Reducing Antioxidant Potential (FRAP), superoxide dismutase, glutathione. RESULTS: The P. tenellus extract did not induce cytotoxicity on murine NIH 3 T3 cells up to 200 μg/mL for 48 h. Besides, level of glutathione was higher in the extract treated NIH 3 T3 cells. P. tenellus extract did not cause mortality at all tested concentration. When treated with 1000 mg/kg of the extract, serum liver enzymes (ALP and ALT) and LDH were lower than normal control and mice treated with 200 mg/kg of extract. Moreover, SOD, FRAP and glutathione levels of liver of the mice treated with 200 and 1000 mg/kg of extract were higher than the normal control mice. On the other hand, when treated with 3000 mg/kg of extract, serum liver enzymes (ALP and ALT) and LDH were higher than normal mice without changing the liver SOD and glutathione level, which may contribute to the histological sign of ballooning hepatocyte. CONCLUSION: P. tenellus extract standardized with 7.9% hydrosable tannins and their catabolites increased the antioxidant levels while reducing the nitric oxide levels in both liver and kidney without causing any acute and sub-chronic toxicity in the mice.